Unprecedented ferromagnetic Gd⋯nitronyl nitroxide coupling through a hydrogen bonding bridge. Issue 31 (20th July 2017) - Sun, Juan; Yang, Meng; Sun, Zan; Wang, Xiufeng; Ma, Yue; Li, Licun
Abstract : An unexpected Gd⋯NO ferromagnetic coupling mediating via a hydrogen bonding interaction is observed in a novel Gd–nitronyl nitroxide chain. Abstract : A novel lanthanide(iii )–nitronyl nitroxide chain {[Gd(hfac)3 (Nit-Ph-3, 5-bIm)(H2 O)]·C4 H10 O} n (1 ) was prepared and characterized. Strikingly, an unexpected ferromagnetic coupling between the Gd(iii ) ion and the nitroxide group mediated by hydrogen bonding has been observed for the first time.